A novel variant in SMG9 causes intellectual disability, confirming a role for nonsense-mediated decay components in neurocognitive development - Rahikkala Elisa; Urpa Lea; Ghimire Bishwa; Topa Hande; Kurki Mitja I.; Koskela Maryna; Airavaara Mikko; Hämäläinen Eija; Pylkäs Katri; Körkkö Jarmo; Savolainen Helena; Suoranta Anu; et al. (SpringerNature, 2022)
Biallelic loss-of-function variants in the SMG9 gene, encoding a regulatory subunit of the mRNA nonsense-mediated decay (NMD) machinery, are reported to cause heart and brain malformation syndrome. Here we report five patients from three unrelated families with intellectual disability (ID) and a novel pathogenic SMG9 c.551 T > C p.(Val184Ala) homozygous missense variant, identified using exome sequencing. Sanger sequencing confirmed recessive segregation in each family. SMG9 c.551T > C p.(Val184Ala) is most likely an autozygous variant identical by descent. Characteristic clinical findings in patients were mild to moderate ID, intention tremor, pyramidal signs, dyspraxia, and ocular manifestations. We used RNA sequencing of patients and age- and sex-matched healthy controls to assess the effect of the variant. RNA sequencing revealed that the SMG9 c.551T > C variant did not affect the splicing or expression level of SMG9 gene products, and allele-specific expression analysis did not provide evidence that the nonsense mRNA-induced NMD was affected. Differential gene expression analysis identified prevalent upregulation of genes in patients, including the genes SMOX, OSBP2, GPX3, and ZNF155. These findings suggest that normal SMG9 function may be involved in transcriptional regulation without affecting nonsense mRNA-induced NMD. In conclusion, we demonstrate that the SMG9 c.551T > C missense variant causes a neurodevelopmental disorder and impacts gene expression. NMD components have roles beyond aberrant mRNA degradation that are crucial for neurocognitive development.